Building Performance Study : Royal Customs Training College Bukit Bahru, Malacca, Malaysia / Kamaruddin Bujang - Bujang, Kamaruddin (Faculty of Architecture, Planning and Surveying, 1981)
This report is part of the course requirement to obtain a paper of Advanced Diploma in Architecture. It is aimed to provide a general analysis regarding building performance that may help in the designing of the new training centre in Johore Bahru - Royal Customs Academy. The selected building is Royal Customs Training College in Malacca. The evaluation made is mostly through observation and there less investigation through interview and research. Any prejudice statements are the fault of the author to make such conclusion. It is hoped that this finding will help in giving valuable materials for design guidance and to develop to more fruitful method of work. Undoubtedly it is also important for the administrator of the college in planning future development.